Histopathological Findings in Prostatic Chips and its Correlation with Prostate Specific Antigen Levels - Saima Nadeem, Naumana Rehman, Mahum Farooq, Sunia Arif, Safia Rahman, Zakia Rahman, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the pattern of histological findings in prostatic chips obtained from cases of enlarged prostate gland and to correlate the findings with PSA levels. Materials and Methods: It was a cross sectional descriptive study conducted in Northwest General Hospital , Peshawar from 1st January 2018 to 23rd December 2021. A total of 500 male cases with features of enlarged prostate, frequency, urgency and dribbling with mean age of 52 ± 12.3 years (range 45 -80 years) were included in the study. The prostatic biopsy specimens were obtained and PSA levels were done in all cases. The histological specimens were subjected to microscopic examinations and findings were recorded in proforma. The findings were correlated with the PSA levels. Mean and standard deviation were used for quantitative data. Frequency and percentages were used for qualitative data Results: Out of 500 cases of enlarged prostate, benign prostate hypertrophy was seen in 375 (75%) cases. 125 cases (25%) had micro invasive carcinoma prostate . All 375 cases of benign prostate hypertrophy had prostate specific antigen levels less than 4ng. Out of 125 cases of micro invasive carcinoma, 120 (96%) had PSA levels >10ng . Sensitivity of PSA at levels of 10ng/ml for prostatic carcinoma was 96%. Conclusion: Benign prostate hypertrophy is the commonest lesion in cases of prostate pathology. PSA is useful marker to determine the presence or absence of micro invasive carcinoma in patients with prostate hypertrophy. Keywords: Benign prostate hypertrophy, micro invasive carcinoma prostate, prostate specific antigen.